2012
DOI: 10.1113/jphysiol.2012.237321
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyridine receptors actively control gating of ryanodine receptors in resting mouse skeletal muscle fibres

Abstract: Key points• Depolarization of the skeletal muscle membrane elicits a change in the configuration of dihydropyridine receptors that in turn triggers sarcoplasmic reticulum (SR) Ca 2+ release through ryanodine receptors.• At rest, it is assumed, but never demonstrated in adult muscle fibres, that dihydropyridine receptors exert a repressive action on ryanodine receptors that keeps them in a closed state.• By measuring Ca 2+ changes in the SR in voltage-clamp conditions, we report that any interventions designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
1
14
1
Order By: Relevance
“…; Eltit et al . ; Robin & Allard, ). However, in the human tissue in the present study, we found no evidence of a differential loss of DHPRs or indeed of any overall loss of either DHPRs or RyRs in the muscle of the Old subjects; on average, the density of the DHPRs and RyRs in total muscle homogenates from the 11 Old subjects was ∼0.98 and ∼0.96 times, respectively, of that found in the muscle of the 10 Young subjects (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Eltit et al . ; Robin & Allard, ). However, in the human tissue in the present study, we found no evidence of a differential loss of DHPRs or indeed of any overall loss of either DHPRs or RyRs in the muscle of the Old subjects; on average, the density of the DHPRs and RyRs in total muscle homogenates from the 11 Old subjects was ∼0.98 and ∼0.96 times, respectively, of that found in the muscle of the 10 Young subjects (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…We also examined the densities of both the DHPR α1 subunits and the RyRs in the muscle of the Old relative to the Young subjects because it has been reported that there is a loss of DHPRs with age in rodent and rabbit muscle (Renganathan et al 1997;Ryan et al 2000). It has been suggested that such a loss of DHPRs underlies the decreased SR Ca 2+ release seen in both rodent (Wang et al 2000) and human muscle (Delbono et al 1995) and it might also increase SR Ca 2+ leakage because of a decrease in the resting inhibition exerted by the DHPRs on the RyRs (Zhou et al 2006;Eltit et al 2011;Robin & Allard, 2012). However, in the human tissue in the present study, we found no evidence of a differential loss of DHPRs or indeed of any overall loss of either DHPRs or RyRs in the muscle of the Old subjects; on average, the density of the DHPRs and RyRs in total muscle homogenates from the 11 Old subjects was ß0.98 and ß0.96 times, respectively, of that found in the muscle of the 10 Young subjects (Table 2).…”
Section: Dhpr and Ryr Densitiesmentioning
confidence: 99%
“…A likely explanation for the differences in response between swimming and isolated muscle performance is that short bursts of locomotion rely on creatine kinase dynamics to supply ATP and are therefore independent from oxygen consumption, at least in the short term (Gray et al, 2006;Wüst et al, 2013). Additionally, it is possible that burst performance may rely more on the excitation of the muscle rather than on muscle contraction-relaxation dynamics (Robin and Allard, 2012) so that it is more dependent on neural signal transmission than on muscle function per se.…”
Section: Discussionmentioning
confidence: 99%
“…DHPRs are located in the transverse tubule of skeletal muscle clustered in tetrads. Each tetrad interacts with every other RyR1 homotetramer [116], and is activated by sarcolemmal depolarization [31, 116]. Once activated, DHPRs undergo a conformational change that leads to RyR1-mediated Ca ++ release [105, 116].…”
Section: Introductionmentioning
confidence: 99%